The nature of socially responsible communication in Indian companies - Pradhan, Sudeepta; Roy, Subhadip (Business: Theory and Practice, 2011)
Firms today try to act beyond their normal course of business towards the society. No longer is the society just a means of earning profit. Socially responsible firms believe that business and society are interwoven rather than being distinct. Such firms try to act in an ethical and responsible manner towards the society. They have a philanthropic approach towards society and communicate it to the society through advertisements. This study aims at analysing such socially responsible ads. More specifically, the study objectives were to identify the themes of socially responsible communication (SRC) promoted by India firms. To achieve the study objectives 68 print advertisements with SRC were content analysed to determine the focus of such communication. The results suggested that most advertisements were serving a multi-fold purpose. They created awareness for the product as well as for social issues which were largely neglected by the society. The study revealed that SRC advertisements could be classified into five categories i.e. Public Awareness, Environment, Child welfare, Health & Safety and Women Upliftment & Security. The overall results suggested that contemporary marketing communication were having a responsible outlook in order to make the society a better place to live in.